Evaluation of Pile Slab Capacity with Changed Length - Indianto, Andi; Putra, Muhammad Andika Pratama; Yanuarini, Erlina; Sofyan, Rikki; Sukarman (Talenta Publisher, 2026)
One of the bridges on the Serpong-Balaraja Toll Road Section 1a project with the longest span is the Cisadane Bridge, which will use a PCI Girder superstructure with a length of 50.8 meters. A bridge approach road structure using a piling slab is located at Sta 2+500-2+564. The piles on the pile slab are planned with a free standing of 6 meters above ground level, and they are 60 cm in diameter, with 11–12 poles forming each segment. When measurements were taken, the length of the pile slab differed from shop drawings. In order to determine whether the pile slab can still support the working load after a change in length and to allow strengthening if the pile slab installed in the field is weak, it is important to assess the structure's performance. By examining the capacity of the reinforcement on the capping beam and the capacity of the spun pile. The evaluation is carried out using analytic software SAP2000. The results of the study for changes in the length of the pile slab structure show that the structure is still adequate because the capacity of the reinforcement on the capping beam installed in the field, namely D19-150, is still sufficient when compared to the results of the analysis, namely D19-153.38. In addition, the spun pile is still adequate because the moment that occurs is still below the permissible moment in the spun pile, which is less than 17 tons.